Routledge encyclopedia of philosophy CD-ROM - Craig, Edward (Routledge, 1998)
Contains over 2,000 articles on a broad range of philosophical topics, from all continents and all periods. Includes searching, navigation, and browsing features. Suitable for users from a wide variety of backgrounds and interests.